A.
3 × 5 - (5 - 12)
= (3 × 5) - (5 - 12)
= 15 - (5 - 12)
= 15 - (-7)
= 15 + 7
= 22
B.
5 - (3 - 5 × 6)
= 5 - (3 - (5 × 6))
= 5 - (3 - 30)
= 5 - (-27)
= 5 + 27
= 32
C.
4 × (2 - 3 × 9) + 7
= 4 × (2 - (3 × 9)) + 7
= 4 × (2 - 27) + 7
= 4 × (-25) + 7
= -100 + 7
= -93
D.
9 × (-2 - 4 × 5) - 3
= 9 × (-2 - (4 × 5)) - 3
= 9 × (-2 - 20) - 3
= 9 × (-22) - 3
= -198 - 3
= -201
E.
63 ÷ (2 - 3 × 7 + 5 × 2) - 11
= 63 ÷ (2 - (3 × 7) + (5 × 2)) - 11
= 63 ÷ (2 - 21 + 10) - 11
= 63 ÷ (-9) - 11
= (63 ÷ (-9)) - 11
= -7 - 11
= -18
F.
48 ÷ (2 - 12 ÷ 4 - 7) - 4
= 48 ÷ (2 - (12 ÷ 4) - 7) - 4
= 48 ÷ (2 - 3 - 7) - 4
= 48 ÷ (-8) - 4
= (48 ÷ (-8)) - 4
= -6 - 4
= -10